New silicate-substituted hydroxyapatite materials doped with silver ions as potential antifungal agents - Agata Piecuch; Sara Targońska; Justyna Rewak-Sorczyńska; Rafał Ogórek; Rafal J. Wiglusz (BMC Microbiology, 2023)
Abstract Background Hydroxyapatites (HAp) are widely used as medical preparations for e.g., bone replacement or teeth implants. Incorporation of various substrates into HAp structures could enhance its biological properties, like biocompatibility or antimicrobial effects. Silver ions possess high antibacterial and antifungal activity and its application as HAp dopant might increase its clinical value. Results New silicate-substituted hydroxyapatites (HAp) doped with silver ions were synthesized via hydrothermal methods. The crystal structure of HAp was investigated by using the X-ray powder diffraction. Antifungal activity of silver ion-doped HAp (with 0.7 mol%, 1 mol% and 2 mol% of dopants) was tested against the yeast-like reference and clinical strains of Candida albicans, C. glabrata, C. tropicalis, Rhodotorula rubra, R. mucilaginosa, Cryptococcus neoformans and C. gattii. Spectrophotometric method was used to evaluate antifungal effect of HAp in SD medium. It was shown that already the lowest dopant (0.7 mol% of Ag+ ions) significantly reduced fungal growth at the concentration of 100 µg/mL. Increase in the dopant content and the concentration of HAp did not cause further growth inhibition. Moreover, there were some differences at the tolerance level to Ag+ ion-doped HAp among tested strains, suggesting strain-specific activity. Conclusions Preformed studies confirm antimicrobial potential of hydroxyapatite doped with silver. New Ag+ ion-HAp material could be, after further studies, considered as medical agent with antifungal properties which lower the risk of a surgical-related infections.